1995
DOI: 10.2136/sssaj1995.03615995005900050026x
|View full text |Cite
|
Sign up to set email alerts
|

Pedogenesis of Cotiga Mound, a 2100‐Year‐Old Woodland Mound in Southwest West Virginia

Abstract: Cotiga Mound, an Early Woodland mortuary mound constructed 2100 YBP, was sampled to evaluate diagnostic horizon development during a well‐defined, relatively short period of time. Five columns (profiles), three of which extended into the submound terrace soil, and one Giddings core of the terrace soil were sampled for particle‐size, pH, organic C, and micromorphology analysis. Six additional cores were collected to characterize the terrace soil. The mound was constructed of acid, silty material, in a manner th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…The Bt horizon of the natural soil has a sufficient clay increase, as well as clay films on ped surfaces to classify it as an argillic horizon (Soil Survey Staff, 1999). No pedogenic characteristics were found between the base of the terrace solum and a depth of 5 m. The age of the terrace was estimated at 5000-8000 years, based on pedogenic development (Cremeens, 1995). Figure 1 for site-specific northing grid.…”
Section: Site Location and Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The Bt horizon of the natural soil has a sufficient clay increase, as well as clay films on ped surfaces to classify it as an argillic horizon (Soil Survey Staff, 1999). No pedogenic characteristics were found between the base of the terrace solum and a depth of 5 m. The age of the terrace was estimated at 5000-8000 years, based on pedogenic development (Cremeens, 1995). Figure 1 for site-specific northing grid.…”
Section: Site Location and Settingmentioning
confidence: 99%
“…On a microscopic scale, the c/f-RDP of most of the mound fill samples are open to double-spaced a porphyric reflection of the silty texture of the mound materials (Cremeens, 1995). A few samples contained a c/f-RDP grading to either enaulic or gefuric.…”
Section: Micromorphology Descriptions Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While studying soils in Pennsylvania, Bilzi and Ciolkosz (1977) found that between 2000 and 3000 years were required on a stable geomorphic surface and in noncalcareous parent materials for processes of soil genesis to translocate enough clay particles from surface soil horizons to form a detectable subsoil clay-enriched horizon. Cremeens (1995) reported the results of a study of soil genesis on a 2 100-year-old Native American mound in southwest West Virginia. On the geomorphically stable mound crest, soil genesis had produced horizons to a depth of 0.75 to 1.0 m. He found that very little clay movement took place during 2100 years.…”
Section: Development Of Chemical Horizonsmentioning
confidence: 99%
“…The degree of soil horizon development, particularly diagnostic subsurface horizons, has been used to infer the chronologic age of alluvial landscapes when calibrated with radiocarbon and artifact dating (Bilzi and Ciolkosz, 1977;Cremeens, 1995;Foss et al, 1995). Diagnostic subsurface horizons provide geoarchaeological investigations with an important tool for defining and correlating geomorphic units in alluvial settings (Ferring, 1992;Foss et al, 1995).…”
Section: Introductionmentioning
confidence: 99%